Pengaruh Model Guided Discovery Learning terhadap Peningkatan Keterampilan Berpikir Kritis Siswa pada Pembelajaran PAI dan Budi Pekerti Kelas VIII di SMP Negeri 1 Candung - Arafah, Mutiara; Muliati, Indah (Lembaga Yasin AlSys, 2025)
This study is motivated by the low critical thinking skills of students in Islamic Education learning at SMP Negeri 1 Candung, where many students tend to be passive and have difficulty analyzing and concluding information. The purpose of this study is to determine the effect of the Guided Discovery Learning model on the critical thinking skills of eighth-grade students at SMP Negeri 1 Candung. This research employs a correlational quantitative method involving 131 students. Data were collected through daily quiz scores and a critical thinking questionnaire. The results indicate that students achieved an average score of 82.37, exceeding the minimum competency standard of 70. The average score for critical thinking skills is 74.45, which falls within the good category. Statistical analysis shows a significant but weak positive correlation between the learning model and students' critical thinking skills. These findings suggest that the Guided Discovery Learning model contributes positively to improving students' critical thinking skills in Islamic Education subjects. This indicates the need for a broader application of discovery-based learning models in Islamic education to enhance students' analytical abilities and engagement.